The illusion of inclusion: examining the limitations of diversity metrics in baseball - Malcomb, Claire Sandman; Zitek, Emily (Frontiers in Psychology, 2025)
The importance of diversity, equity, and inclusion (DEI) in sports has become widely discussed in recent years, and many sports organizations have dedicated extensive resources to DEI initiatives. Much of the focus has been on the representation of underrepresented minorities within sports, and many organizations rely heavily on representation as a metric for success of their DEI initiatives. In the current work, we examine the potential limitations of diversity metrics currently used in professional sports organizations. Recently, reports have suggested that player and coach diversity in Major League Baseball are good, with high international Latino representation, and DEI efforts should therefore be focused elsewhere. However, across two studies utilizing datasets of Major and Minor League Baseball players (Study 1) and coaches (Study 2), we find evidence that, despite the high diversity, some baseball players and coaches in the lower levels seem to have less ability to advance than others. Specifically, international Latino players are less likely to make it to as high of a level in baseball as US-born players, and international Latino coaches are more likely to get stuck in the lower levels of coaching. Moreover, in a third study surveying players in the independent Frontier League, we find evidence that non-White players feel less of a sense of inclusion. We provide insight and recommendations for how sports organizations and researchers can better measure and interpret the progress of DEI initiatives in sports.